The Charism of 21st-Century Catholic Schools: Building a Culture of Relationships - Cook, Timothy J.; Simonds, S. J., Thomas A. (Catholic Education: A Journal of Inquiry and Practice, 2011)
Catholic schools are called to embody an identity and charism that make a unique and meaningful contribution to our Church and society. In the article, the authors present a coherent and relevant framework for thinking about Catholic identity and charism in contemporary schools using relationships as the organizing principle. The authors assert that 21st-century Catholic schools can provide a much needed and appealing charism for today’s world by building a culture of relationships. The authors’ framework deals specifically with a student’s relationship with self, God, others, the local and world community, and creation, as well as a student’s ability to critique culture through the lens of faith. The framework draws on ecclesial documents, scholarship, and current educational practice.